Abordajes psicoanalíticos a inquietudes sobre la subjetividad IV - Murcia Zorrilla, María del Pilar (Señales, 2021)
From the moment it came out in 2012, Psychoanalytic Approaches to Concerns about Subjectivity set out to bring together a certain diversity of topics and invite national and international authors, thus consolidating a project that should be attractive not only to the academic public of the psychoanalytic field, but also to all those who wish to approach, establish a dialogue or address certain epistemological, scientific and theoretical issues in the field of psychoanalysis. In this new volume, the reader will find three sections that the editors have called conceptual theoretical reviews; contemporary problems of clinical practice; and psychoanalysis applied to the understanding of social conflicts.